PROFIL STATUS GIZI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2012 DAN 2013 BERDASARKAN INDEKS MASSA TUBUH, WAIST HIP RATIO DAN LINGKAR PINGGANG - Jannah, Wirdhatul; Bebasari, Eka; Ernalia, Yanti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTNutritional status is the standard about person's body condition that can be seen from the food consumed and the nutrients used by the body. The problems of nutritional status are undernutrition and overnutrition. Most of people in the city had overnutrition status. Nutritional status can be measured by antropometry. This research were done to figure out the nutritional profile of medical Faculty University of Riau students class 2012 and 2013 based on body mass index, waist hip ratio and waist circumference. This research was designed using descriptive cross sectional methode that amounted 238 students. The result were found age group 19 years old as many as 117 students (49,2%), mostly female as many as 192 students (80,7%). Based on body mass index showed 49,2% students include normal category, obesity 23,9%, overweight 16,0% and underweight 10,9%. Based on waist hip ratio showed 55,9% were found not obese and 44,1% include obesity and based on waist circumference showed 80,3% were found not obese and 19,7% include obesity.Key words: Body Mass Index, Waist Hip Ratio, Waist Circumference